Computer modelling of atomic-molecular states leading to Maxwell distribution - Sadovyi, M I; Riezina, O V; Tryfonova, O M; Donets, N V (Journal of physics. Conference series, 2025)
This article examines the dynamics of transitioning from the traditional educational model focused on information accumulation to an innovative information model emphasizing the development and quality of research outcomes within smart educational environments. This approach facilitates the integration of computational resources with the cyber-physical nature of natural phenomena. We address the challenge of computer modelling atomic-molecular gas states subject to Maxwell distribution laws, employing an integrative method of simulated visual-dynamic computer modelling developed using Python’s Matplotlib module. The resulting visualization, termed integrative presentation-dynamic computer visualization, enables the creation of Python programs that construct models of Maxwell’s graphical simulated dynamic distribution. The adjustable parameters within these models provide new insights into the physical essence of molecular velocity distributions. Through this approach, students develop an autonomous worldview oriented toward independent truth-seeking and scientific inquiry.